Using Technology in Fragile, Conflict, and Violence Situations : Five Key Questions to be Answered - Garber, Kent (World Bank, Washington, DC, 2018)
Many technologies are now widely used by humanitarian and development partners to collect data, improve planning and project implementation, and strengthen monitoring and evaluation in fragile and conflict-affected contexts and many other technologies are in the pipeline. Within the World Bank, there is growing interest to incorporate technology more strongly into FCV projects; at the same time, there is also a recognition that technology is not a “one size fits all” solution, and some technologies may be more appropriate for certain contexts than others. This note offers some basic guidance to Task Team Leaders (TTLs) on how to approach this “new frontier” when considering the use of technology in FCV health projects. Five key questions to be answered: i) What challenges can technology help address in FCV settings?; ii) What basic enabling factors should be assessed for technologies in FCV settings?; iii) What risks and limitations should be considered with these technologies?; iv) How have technologies been used in World Bank FCV health projects? and v) What disruptive technologies are on the horizon?